2020
DOI: 10.2478/jtim-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 and MiR-665 role as potential non-invasive biomarkers for hepatocellular carcinoma in Egyptian patients with chronic hepatitis C virus infection

Abstract: Background and ObjectivesHepatocellular carcinoma (HCC) is the fourth leading cause of cancer associated death globally. Serum micro RNAs are full of potential as noninvasive biomarkers. Here, we aim to assess the performance of serum MicroRNA-155 and MicroRNA-665 as diagnostic biomarker for HCC comparing to AFP.MethodsSerum samples were collected from 200 subjects (40 healthy control, 80 chronic hepatitis C patients with cirrhosis and without HCC (LC) and 80 HCC patients currently infected by hepatitis C infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…The lncRNA AC007099.1 was found to be differentially expressed in hepatocellular carcinoma exosomes. miRNA is an important risk marker for HCC and liver injury [ 40 , 41 ]. When lncRNAs and mRNAs have the same microRNA response element (MRE), there is competition between them for the same kind of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA AC007099.1 was found to be differentially expressed in hepatocellular carcinoma exosomes. miRNA is an important risk marker for HCC and liver injury [ 40 , 41 ]. When lncRNAs and mRNAs have the same microRNA response element (MRE), there is competition between them for the same kind of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] The immune signature identified novel targets and was exploited for immunotherapies to predict the benefit of immunotherapeutic drugs. [ 18 - 20 ] Currently, noncoding RNA is also being reported as an effective cancer biomarker; [ 21 ] these signatures provided clues for both precise individual clinical treatment and drug development and also provided the basis for the inclusion and exclusion criteria of the population for clinical trials of new targeted drugs. In the present study, we focused on the ITG family, which is considered as one of the important families for cellular biological behaviors; [ 22 , 23 ] however, our results demonstrated that only ITGA5, ITGA6, and ITGAL were the prognostic factors in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the most important therapeutic approach for patients with hepatocellular carcinoma (HCC), but the rate of postoperative recurrence and metastasis is relatively high. Sorafenib is a commonly used chemotherapeutic drug against HCC, but it is difficult to clinically determine the prognosis of HCC and reduce sorafenib resistance[ 69 ]. Shan et al [ 70 ] analyzed two different public HCC databases and found that ubiquitin-like modifier activating enzyme 1 (UBA1) can regulate ferroptosis in HCC cells via the Nrf2 pathway.…”
Section: Ferroptosis and Gi Diseasesmentioning
confidence: 99%